(untitled) (Research, Society and Development, 2020)
The objective of this article is to report the experience of academics, health professionals and teachers in the construction of a Singular Therapeutic Project with one person in mental suffering, in the context of Primary Health Care. It is an experience report about the process of construction of a Singular Therapeutic Project using the reference of psychosocial care and rehabilitation, with the participation of the user and her family, medical and nursing students, teachers, Health Strategy team Family (ESF), and the team of the Psychosocial Care Center in the user’s territory. The Singular Therapeutic Project considered the singularities and the social context of the user, generating the integration of the services of the Psychosocial Care Network, and a collaborative, dialogical and psychosocial care. Therefore, the Singular Therapeutic Project allowed the care and psychosocial rehabilitation of a user with mental suffering and the strengthening of interprofessional work in a primary care service.